Near infrared emission and multicolor tunability of enhanced upconversion emission from Er3+-Yb3+ co-doped Nb2O5 nanocrystals embedded in silica-based nanocomposite and planar waveguides for photonics - Aquino, Felipe Thomaz; Ferrari, Jefferson Luis; Maia, Lauro June Queiroz; Ribeiro, Sidney José Lima [UNESP]; Ferrier, Alban; Goldner, Philippe; Gonçalves, Rogéria Rocha (Elsevier, 2016)
This work reports on the Yb3+ ion addition effect on the near infrared emission and infrared-to-visible up conversion from planar waveguides based on Er3+-Yb3+ co-doped Nb2O5 nanocrystals embedded in SiO2-based nanocomposite prepared by a sol-gel process with controlled crystallization in situ. Planar waveguides and xerogels containing Si/Nb molar ratio of 90:10 up to 50:50 were prepared. Spherical-like orthorhombic or monoclinic Nb2O5 nanocrystals were grown in the amorphous SiO2-based host depending on the niobium content and annealing temperature, resulting in transparent glass ceramics. Crystallization process was intensely affected by rare earth content increase. Enhancement and broadening of the NIR emission has been achieved depending on the rare earth content, niobium content and annealing temperature. Effective Yb3+→Er3+ energy transfer and a high-intensity broad band emission in the near infrared region assigned to the Er3+ ions 4I13/2→4I15/2 transition, and longer 4I13/2 lifetimes were observed for samples containing orthorhombic Nb2O5 nanocrystals. Intense green and red emissions were registered for all Er3+-Yb3+ co-doped waveguides under 980 nm excitation, assigned to 2H11/2→4I15/2 (525 nm),4S3/2→4I15/2 (545nm) and 4F9/2→4I15/2 (670 nm) transitions, respectively. Different relative green and red intensities emissions were observed, depending upon niobium oxide content and the laser power. Upconversion dynamics were determined by the photons number, evidencing that ESA or ETU mechanisms are probably occurring. The 1931 CIE chromaticity diagrams indicated interesting color tunability based on the waveguides composition and pump power. The nanocomposite waveguides are promising materials for photonic applications as optical amplifiers and WDM devices operating in the S, C, and L telecommunication bands; and as upconverter materials for visible upconversion lasers, biomedical applications, energy conversion for solar cells and others.
Keywords: Broadband NIR emission; Nb2O5; Sol-gel; Upconversion